A potential technological application of probiotic microcapsules in lactose-free Greek-style yoghurt. (October 2019) - Pinto, Stephanie S.; Fritzen-Freire, Carlise B.; Dias, Carolinne O.; Amboni, Renata D.M.C.
Abstract: The potential of lactose-free Greek-style yoghurt as a new matrix for incorporation of spray-dried microcapsules containing the probiotic Bifidobacterium lactis BB-12 was evaluated. Three different microcapsule formulations were produced using gum arabic, inulin and maltodextrin as wall materials. All formulations showed encapsulation yield above 96% and good probiotic viability (>8 log cfu g −1 ) throughout 30 days of storage (4 °C). Microcapsules produced with gum arabic and inulin showed the best physical properties (lowest moisture, solubility and hygroscopicity values, and highest bulk and tapped densities), and thus were selected to be added to the yoghurt. Addition of the microcapsules increased the product's pH, firmness and adhesiveness; however, it did not affect the viability of the starter cultures. After 30 days of storage, probiotic viability was above 6.5 log cfu g −1, indicating that lactose-free Greek-style yoghurt may be an appropriate matrix for B. lactis BB-12.